Insight into pectin-cation-phytate theory of hardening in common bean varieties with different sensitivities to hard-to-cook. (January 2022) - Wainaina, Irene; Lugumira, Robert; Wafula, Elizabeth; Kyomugasho, Clare; Sila, Daniel; Hendrickx, Marc
Graphical abstract: Highlights: Common bean varieties with different sensitivities to hard-to-cook were explored. Ageing results in hydrolysis of InsP6 to lower inositol phosphates. Hydrolysis of InsP6 during ageing results in Ca 2+ release. Calcium ion migration is mainly occurring during the early phases of cooking in contrast to during ageing and soaking. InsP6 degradation correlates with changes in cooking times and bound Ca 2+ changes. Abstract: In this study, a detailed quantitative analysis of the mechanisms linked with pectin-cation-phytate hypothesis of hard-to-cook development (HTC) was evaluated to assess the plausibility of this hypothesis. Several common bean varieties with varying sensitivities to HTC were characterized for pectin, cell wall bound calcium and inositol hexaphosphate (InsP6 ) content before and after ageing. Ageing resulted in a significant decrease in InsP6 content (resulting in calcium release) in all varieties. Despite not significantly changing during ageing, the cell wall bound calcium content significantly increased in most aged bean varieties upon short cooking indicating enhanced internal cation migration during the early phase of cooking in contrast to during ageing and soaking. Among the parameters evaluated in this study, the relative changes in InsP6 content significantly correlated with the change in cooking times as well as changes in cell wall bound calcium content. Results obtained in this study suggest that in some bean varieties, pectin-cation-phytate hypothesis is the predominant mechanism by which hardening occurs during storage while in other varieties, the role of other factors such as phenolic crosslinking as suggested in literature cannot be ruled out.